Nanostructure Determines the Wettability of Gold Surfaces by Ionic Liquid Ultrathin Films - Borghi, Francesca; Mirigliano, Matteo; Lenardi, Cristina; Milani, Paolo; Podestà, Alessandro (Frontiers in Chemistry, 2021)
Ionic liquids are employed in energy storage/harvesting devices, in catalysis and biomedical technologies, due to their tunable bulk and interfacial properties. In particular, the wettability and the structuring of the ionic liquids at the interface are of paramount importance for all those applications exploiting ionic liquids tribological properties, their double layer organization at electrified interfaces, and interfacial chemical reactions. Here we report an experimental investigation of the wettability and organization at the interface of an imidazolium-based ionic liquid ([Bmim][NTf2]) and gold surfaces, that are widely used as electrodes in energy devices, electronics, fluidics. In particular, we investigated the role of the nanostructure on the resulting interfacial interactions between [Bmim][NTf2] and atom-assembled or cluster-assembled gold thin films. Our results highlight the presence of the solid-like structured ionic liquid domains extending several tens of nanometres far from the gold interfaces, and characterized by different lateral extension, according to the wettability of the gold nanostructures by the IL liquid-phase.